Dating Methods of Pleistocene Deposits and Their Problems: VI. Paleomagnetism - Barendregt, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1981)
Summary Paleomagnetism is used in Pleistocenestratigraphie studies as a tool for correla-tion and relative age dating of equivalentstrata or for the absolute dating of depos-its. The method is based on the detectionof changes in the earth's magnetic fieldand especially changes of polarity thatare recorded by ferromagnetic sedimentsat the time of deposition. The study of paleomagnetism as ageophysical dating method began in the1960s and has grown geometricallysince. Instrumentation has greatlyimproved and the statistical analysis ofdata, so essential to the proper interpre-tation of the magnetic record, would nothave been possible without computerfacilities. Fine-grained sediments and lava flowsare the two media most frequently used.Because reversals have occurred repeat-edly in the past, their identification withinincomplete sedimentary records is onlypossible through comparison with otherstratigraphie or radiometric data col-lected for similar or related sedimentarysequences. Continuously depositedmarine or terrestrial sediments whichshow a high sedimentation rate provideisochrons which can be used for world-wide correlation. The recent flourish ofresearch activity into the secular variationof the earth's non-dipole field promises togreatly refine and embellish the geomag-netic time table for the Pleistocene.